ANALISIS TENTANG KERUSAKAN DAN PERAWATAN ALAT BERAT DI DINAS PEKERJAAN UMUM DAN TATA RUANG (DINAS PUTR) - Hermawan, Deden; Rachmat, Asep (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
This abstract highlights the role and significance of the Public Works and Spatial Planning Agency (PUTR) in managing heavy equipment for various infrastructural and construction projects. The agency plays a crucial role in promoting sustainable development and infrastructure management in the region it serves. This abstract aims to provide an overview of the key aspects of PUTR's heavy equipment management practices and its impact on infrastructure development. The Public Works and Spatial Planning Agency (PUTR) is a government institution responsible for overseeing infrastructure development, spatial planning, and environmental management. As part of its core responsibilities, PUTR manages a diverse fleet of heavy equipment used for construction, maintenance, and rehabilitation of roads, bridges, buildings, and other public facilities. PUTR employs a comprehensive approach to heavy equipment management, focusing on strategic planning, acquisition, maintenance, and utilization. The agency collaborates with relevant stakeholders to ensure the efficient allocation and utilization of heavy equipment across different projects. By adopting modern technology and best practices, PUTR aims to enhance operational efficiency, reduce costs, and improve project timelines. The strategic acquisition of heavy equipment is a crucial aspect of PUTR's management approach. The agency conducts thorough assessments to identify the specific needs of different projects and procure equipment accordingly. Additionally, PUTR prioritizes eco-friendly and energy-efficient machinery to support sustainable development and minimize environmental impact. Maintenance plays a pivotal role in prolonging the lifespan of heavy equipment. PUTR implements proactive maintenance programs to ensure the optimal functioning of machinery and prevent unexpected breakdowns. Regular inspections, timely repairs, and adherence to safety standards are prioritized to ensure the safety of workers and the longevity of the equipment. PUTR's effective utilization of heavy equipment significantly influences the pace and quality of infrastructure development. Through streamlined equipment deployment and continuous monitoring, the agency maximizes productivity and minimizes downtime, leading to cost-effective and timely project completion. In conclusion, the Public Works and Spatial Planning Agency (PUTR) plays a critical role in managing heavy equipment for infrastructure development. Its strategic approach to acquisition, efficient maintenance practices, and optimal equipment utilization contribute to the successful implementation of various construction projects. As a result, PUTR's efforts significantly impact the region's overall growth and development while promoting sustainability and environmental responsibility in the realm of heavy equipment management.PUT